User Interface Evaluation and Design Recommendations for the Tulungagung Portal Website Using the Heuristic Evaluation Method - Maula, Sheila Hikmatul; Ramadhan, Viry Puspaning; Jatmiko, Andriyan Rizki (Yayasan Kawanad, 2025)
Government websites serve as essential platforms for delivering information and public services online, yet many still face usability challenges. The present study evaluates the user interface of the Tulungagung Regency Government website and provides interface improvement recommendations. The research utilized a heuristic evaluation method involving three evaluators and applied ten heuristic principles to identify usability issues. Data were collected through direct observation, documentation, and user questionnaires. Interface improvement recommendations were designed as a high-fidelity prototype using Figma. To test the effectiveness of the proposed design, usability testing was conducted using the System Usability Scale (SUS) method involving 25 respondents. The study found key issues including inconsistent visual design, disorganized menu structure, and lack of system feedback. The usability testing results indicated a significant increase in usability scores with the redesigned prototype compared to the original version. The research contributes to the development of more user-friendly government websites and can serve as a reference for similar interface evaluations in the public sector.